A multiport superconducting fault‐current‐limiting circuit breaker for a flexible DC power grid. Issue 3 (7th July 2021) - Wang, Weiru; Wang, Limeng; He, Zhiyuan; Xin, Yechun; Li, Guoqing
Abstract: The fault current of the high‐voltage and large‐capacity flexible DC power grid has the characteristics of a fast rising rate, high peak value, and large influence area; therefore, fault current suppression equipment suitable for the flexible DC power grid has become a research hotspot. First, the fault mechanism and fault current calculation associated with the DC converter are analysed in this study; subsequently, a multiport superconducting fault‐current‐limiting circuit breaker (SFCLCB) suitable for a flexible DC power grid is designed. The circuit breaker adopts ground drainage to transfer the fault current. It only needs to be equipped with a single‐way conduction power electronic switch group and the number of switches is not affected by the number of DC lines, considerably improving the cost effectiveness of the equipment. In addition, the workflow and current‐limiting principle of SFCLCB are analysed, and the optimal matching method is determined with respect to the resistance of the superconducting current limiter and the power electronic devices of the main circuit breaker. Afterwards, the four‐terminal flexible DC transmission simulation system is observed to exhibit high efficiency in suppressing the fault current and high cost effectiveness based on comparative simulations. Finally, its engineering applicability is verified by the digital physical and hybrid simulation platform.